Les frontières religieuses dans le Brésil du xvie siècle : le chamanisme colonial des missionnaires jésuites et des Indiens tupinamba - Charlotte de Castelnau-L’Estoile (Cahiers des Amériques Latines, 2011)
In this article the author analyses the process of evangelization of the Tupinamba Indians on the Brazilian coast in the second half of the 16th century. It aims to show how the method of adaptation or accommodation was used by the Jesuits to evangelize the Indians considered as people "without faith, law and king". Although they denounced the absence of religion of these Indians, the missionaries defined a religious frontier in 16th century Brazil. Shamanism was then observed, described and sometimes imitated by the Jesuits, who were criticized, especially by the first bishop of Brazil. The article focuses on the figure of Francisco Pinto, a missionary in the northern frontiers of 17th century Brazil, on the limits of the colonial territory. Francisco Pinto was an ambivalent cross-border figure, who used his excellent knowledge of the Indian language and became a kind of shaman himself and ended murdered by hostile Indians. Jesuit Portuguese documents, as well as French Capuchin sources, provide the sources to analyze both Pinto’s missionary methods and Indian logic at work in this interactive episode.